2018
DOI: 10.1111/anu.12667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary selenium on growth performance and oxidative stress in juvenile grass carpCtenopharyngodon idellus

Abstract: An 8‐week feeding trial was conducted to investigate the effect of dietary selenium (Se) on feed intake, weight gain and antioxidant activity in juvenile grass carp (11.2 ± 0.03 g). Six Se levels (0.13, 0.41, 0.56, 1.12, 2.18 and 4.31 mg/kg) of semi‐purified diets were assayed in triplicate. The maximum weight gain, specific growth rate and feed intake were obtained in fish fed with 1.12 mg Se/kg diet. Hepatic glutathione peroxidase activity was markedly increased when dietary Se ≤1.12 mg/kg diet and reached a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…The growth parameters (final average weight, WG and SGR) of the loach Paramisgurnus dabryanus (Sauvage) were not significantly affected by diet Se‐chitosan (Victor et al, ), and the growth performance of pacu ( Piaractus mesopotamicus ) was not significantly affected by different levels of Se‐yeast in diet (Takahashi et al, ). And the decreased growth rate in fish fed diet with 0.3 mg/kg Nano‐Se can be explained by the significantly reduced intraperitoneal fat and lipid content in hepatopancreas (not shown data), and this effect of Se on lipid accumulation has been reported by previous study (Liu et al, ). The survival rate of the fishes significantly increased compared to the control group when dietary Nano‐Se levels reached 0.6 mg/kg, and the improved antioxidant capacity of fishes (see details in section 3.3) might partially account for this positive effect.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The growth parameters (final average weight, WG and SGR) of the loach Paramisgurnus dabryanus (Sauvage) were not significantly affected by diet Se‐chitosan (Victor et al, ), and the growth performance of pacu ( Piaractus mesopotamicus ) was not significantly affected by different levels of Se‐yeast in diet (Takahashi et al, ). And the decreased growth rate in fish fed diet with 0.3 mg/kg Nano‐Se can be explained by the significantly reduced intraperitoneal fat and lipid content in hepatopancreas (not shown data), and this effect of Se on lipid accumulation has been reported by previous study (Liu et al, ). The survival rate of the fishes significantly increased compared to the control group when dietary Nano‐Se levels reached 0.6 mg/kg, and the improved antioxidant capacity of fishes (see details in section 3.3) might partially account for this positive effect.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies have found that optimal Se in diets improved the growth performance of fish. About 0.83 mg/kg of dietary sodium selenite can significantly improve the growth of juvenile grass carp (Liu et al, ). Also, 1 mg/kg of dietary Nano‐Se can improve fish growth and antioxidant defence of common carp ( Cyprinus carpio ) (Ashouri et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a recent metabolomics study on Atlantic salmon implied that dietary Se may affect the abundance of pathway alteration in lipid metabolism (Berntssen et al, ). A previous study also showed that the whole body crude fat content was decreased and then increased with the increasing dietary Se in juvenile grass carp (Liu et al, ). The specific mechanism of Se on fish lipid metabolism deserves further investigations.…”
Section: Discussionmentioning
confidence: 77%
“…However, hepatopancreatic MDA content did not decrease at Se level of 0.57 mg/kg, while which owns the highest hepatopancreatic and serum GPx activity. In previous studies, MDA was negatively correlated with increasing GPx activity in common carp and gibel carp with Se supplement (Liu et al, ; Saffari, Keyvanshokooh, Zakeri, Johari, & Pasha‐Zanoosi, ). The increased hepatopancreatic SOD at dietary Se levels of 0.79 and 1.00 mg/kg may compensate for the lack of greater expression of GPx in this study, as SOD was reported to combat oxidative stress in conjunction with GPx in the antioxidant systems (Zee, Patterson, Wiseman, & Hecker, ).…”
Section: Discussionmentioning
confidence: 80%